Persepsi Pemilih terhadap Kinerja Kepala Desa di Desa Sidodadi Kecamatan Biru-Biru Kabupaten Deli Serdang - Satya Nofryanti N.; Rosaria Anastasya Br Sianipar; Julia Ivana (Journal on Education, 2024)
This research aims to determine and describe voters' perceptions of the performance of village heads in Sidodadi village, Biru-Biru subdistrict, Deli Serdang Regency. This research method is a type of research using qualitative descriptive research. Data collection techniques use literature studies and field research consisting of observations and interviews. The data analysis used is a qualitative data analysis method as a form of analysis. The results of this research show that voters' perceptions of the performance of the village head in Sidodadi Village, Biru-Biru District, Deli Serdang Regency are quite good, but there are several things that need to be improved. The quality of performance in public services in Sidodadi village is still inadequate and does not meet community expectations. In terms of transparency of village funds, the Sidodadi village head is expected to be more transparent in their management in order to increase trust in the village residents.